2000
DOI: 10.1034/j.1600-0455.2000.041004322.x
|View full text |Cite
|
Sign up to set email alerts
|

MR IMAGING IN CLINICALLY SUSPECTED ACUTE CHOLECYSTITIS. A comparison with ultrasonography

Abstract: MR has a higher sensitivity than US for diagnosing acute cholecystitis and, with increased accessibility, may be the first imaging method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Although MR findings of acute cholecystitis, chronic cholecystitis and gallbladder carcinoma have been reported [5,6,[13][14][15][16][17], to our knowledge, MR imaging findings in large series of patients with gallbladder disease and the schematic analysis of MR imaging findings for gallbladder wall thickening have not been well documented. Therefore, the purpose of this study was to correlate the MR findings of gallbladder wall thickening with the pathologic findings on the basis of the layered pattern and to evaluate the diagnostic value of HASTE MR imaging in gallbladder disease.…”
Section: Figmentioning
confidence: 94%
“…Although MR findings of acute cholecystitis, chronic cholecystitis and gallbladder carcinoma have been reported [5,6,[13][14][15][16][17], to our knowledge, MR imaging findings in large series of patients with gallbladder disease and the schematic analysis of MR imaging findings for gallbladder wall thickening have not been well documented. Therefore, the purpose of this study was to correlate the MR findings of gallbladder wall thickening with the pathologic findings on the basis of the layered pattern and to evaluate the diagnostic value of HASTE MR imaging in gallbladder disease.…”
Section: Figmentioning
confidence: 94%
“…As with CT, MRI is not advocated as a primary imaging examination to evaluate acute right upper quadrant pain; however, several studies have suggested that abdominal MRI is a reliable alternative and can be particularly helpful in patients who are difficult to examine with ultrasound [2123]. Although factors such as longer acquisition times limit its use in the emergency setting, less interpreter variability and more consistent visualization of the extrahepatic biliary tree are important advantages of its use [24, 25]. MRI can be the next best imaging modality when AC is excluded, and it is considered the best modality for evaluating hepatic and biliary abnormalities that are not characterized by ultrasound.…”
Section: Summary Of Literature Reviewmentioning
confidence: 99%
“…In particular, T2W sequences with and without fat saturation have shown superior image quality also in patients who were not cooperative. Furthermore, the T2W HASTE sequences have a high sensitivity to oedema and fluid collections, which sensitivity is of great value in diagnosing inflammatory conditions and post‐operative surgical complications (4, 10, 11, 17, 21, 23).…”
Section: Discussionmentioning
confidence: 99%